Extreme weather and undernutrition: A critical but constructive review of the literature - Headey, Derek D.; Venkat, Aishwarya (International Food Policy Research Institute, 2024)
Climate change is resulting in increased frequency of extreme weather events, especially in low- and middle-income countries (LMICs) already characterized by highly vulnerable malnourished populations. Unsurprisingly, there are many empirical studies of the linkages between extreme weather events and undernutrition, especially stunting and wasting in early childhood, and several existing reviews of this literature. However, the quality of empirical studies in this highly multi-disciplinary literature is uneven, and existing reviews do exhaustively illustrate the potential pitfalls of climate-nutrition analyses. In this more critical review, we therefore have five objectives. First, to map out the existing literature, particularly in terms of the types of dependent and independent variables used, the geographies in which different studies focus their analysis, and the types of statistical methods used. Our second objective is to illustrate the empirical limitations and pitfalls of this literature through a more critical review. Our third objective is to be critically constructive, by developing a checklist of good practices for analytical studies in this literature, which we hope will be formalized and broadly adopted. Our fourth objective is to illustrate the usefulness of these good practices through a deep dive into what we consider an exemplary study in the literature from Blom et al. (2022). Our final objective is to identify possible steps for new types of survey methods and data collection, actions for the adoption of best-practice analytical methods and identify important research questions for future research.